1987
DOI: 10.1099/0022-1317-68-8-2117
|View full text |Cite
|
Sign up to set email alerts
|

The Nucleotide Sequence and Genome Organization of Bovine Papillomavirus Type 4

Abstract: SUMMARYThe nucleotide sequence of bovine papillomavirus type 4 (BPV-4) was determined. The viral genome is 7261 base pairs long. Several overlapping open reading frames (ORFs) have been identified both on the basis of amino acid comparison with other papiUomaviruses and on their transcriptional pattern. Eight early ORFs (E 1 to 8) were recognized, coding for DNA replication and cell transformation functions, and three late ORFs (L1 to 3), coding for structural proteins. Like the E50RF of human papillomavirus t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
3

Year Published

1988
1988
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 41 publications
(45 reference statements)
0
16
1
3
Order By: Relevance
“…Since the ORFs are not homologues we have continued with the E8 nomenclature. Other small, putative ORFs include BPV-3 L3 and RPV E9, homologous to BPV-4 L3 (Patel et al, 1987) (41 % amino acid identity) and EEPV E9 (Eriksson et al, 1994) (45 % amino acid identity), respectively. The atypical and rare ORFs (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Since the ORFs are not homologues we have continued with the E8 nomenclature. Other small, putative ORFs include BPV-3 L3 and RPV E9, homologous to BPV-4 L3 (Patel et al, 1987) (41 % amino acid identity) and EEPV E9 (Eriksson et al, 1994) (45 % amino acid identity), respectively. The atypical and rare ORFs (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of the 754 nucleotide (nO sequence of cDNA 7El 1 with the BPV-4 genomic sequence (Patel et al, 1987) revealed two regions of homology. The 5' end of the cDNA was located at nt 943, but contiguous homology with the viral genome ended at nt 1016, a consensus splice donor site (Breathnach & Chambon, 1981).…”
Section: Sequence Analysis Of Cdna 7ellmentioning
confidence: 99%
“…The major transcripts are thought to express the E4 protein of BPV-4, while the minor species may encode transcription-regulating proteins. The nucleotide sequences of BPV-4 cDNAs precisely located the early polyadenylation site, and in addition led to alterations in the previously reported genomic sequence and organization of BPV-4 (Patel et al, 1987). Two new promoters were identified and a candidate sequence for the control of transcription from the heterogeneous late RNA start site of papillomaviruses is proposed.…”
Section: Introductionmentioning
confidence: 99%
“…A GC box, present within the limits of NR2 defined by the deletion analysis, was initially identified as a potential binding site for the trans-activator Spl (Patel et al, 1987). However, Kageyama & Pastan (1989) have identified a transcriptional repressor, GCF, in human cells which binds to GC-rich sequences, the consensus binding sequence being GCGGGGC.…”
Section: Discussionmentioning
confidence: 99%
“…The viral genome is 7265 nucleotides long and can be roughly divided into two sections, encoding the early and late viral proteins. Upstream of the early region is a long control region (LCR) which contains potential binding sites for several factors, including NF 1, Sp 1 and the viral trans-activator E2 (Patel et al, 1987). By analogy with BPV-1, which is able to transform mouse cells in vitro although it does not cause cancer in vivo (Broker & Botchan, 1986), both positive and negative regulation of the BPV-4 LCR might be expected to occur via the action of full-length (trans-activator) and short (repressor) E2 molecules binding at the E2 sites (Lambert et al, 1989).…”
Section: Introductionmentioning
confidence: 99%